Pushing the Envelope: A Unique Case of Successful Treatment of Diquat Poisoning with Multiorgan Dysfunction - Varghese, George; Patil, Navin; Gurung, Shanti; Bakkannavar, Shankar M; Rao, Karthik; Nazeer , Mohsin (Journal of Indian Academy of Forensic Medicine, 2020)
Consumption of chemicals and toxins is one of the most common means of committing suicide. Ingestion of pesticides for commission of suicide is a common subtype of this. Pesticide poisoning cases continue to be the one of the most important therapeutic problems around the world. We report a case of suicidal diquat (1,1’-ethylene-2,2’- bipyridyldiylium) poisoning that presented itself with complications and multi-organ failure. The patient was riddled with a myriad of problems such as vomiting, diarrhoea, painful burning of the mouth, tongue oedema, somnolence, mydriasis, reduced light re-flexes, jaundice and hematuria. Timely hemoperfusion, intravenous N acetyl cysteine and transfusion of blood products to the patient prevented catastrophic haemorrhage and saved his life. The patient was successfully treated and fully recovered. In this paper the medical line of management was highlighted which was responsible for the recovery.